2016
DOI: 10.1021/jacs.6b00088
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical Nitridation with Anion Vacancy-Assisted N3–/O2– Exchange

Abstract: We present how the introduction of anion vacancies in oxyhydrides enables a route to access new oxynitrides, by conducting ammonolysis of perovskite oxyhydride EuTiO3-xHx (x ∼ 0.18). At 400 °C, similar to our studies on BaTiO3-xHx, hydride lability enables a low temperature direct ammonolysis of EuTi(3.82+)O2.82H0.18, leading to the N(3-)/H(-)-exchanged product EuTi(4+)O2.82N0.12□0.06. When the ammonolysis temperature was increased up to 800 °C, we observed a further nitridation involving N(3-)/O(2-) exchange,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…However, even at higher temperatures where the hydride has already left, the remaining anion-deficient structure can be useful for further anion-exchange reactions. This has been demonstrated by the formation of EuTiO 2 N by Mikita et al [ 41 ]. Here, EuTiO 2.82 H 0.18 was first prepared.…”
Section: Chemical Reactivity Of Oxyhydrides: Lability and Exchangementioning
confidence: 83%
See 1 more Smart Citation
“…However, even at higher temperatures where the hydride has already left, the remaining anion-deficient structure can be useful for further anion-exchange reactions. This has been demonstrated by the formation of EuTiO 2 N by Mikita et al [ 41 ]. Here, EuTiO 2.82 H 0.18 was first prepared.…”
Section: Chemical Reactivity Of Oxyhydrides: Lability and Exchangementioning
confidence: 83%
“…For Eu [ 30,41 ], or other highly absorbing elements (e.g. Sm, Gd, Dy) NPD should be nonetheless avoided, though not impossible with a special cell arrangement [ 41 ]. High-resolution time-of-flight (TOF) NPD instruments are often more suited than constant-wavelength diffractometers to determine subtle structural features, for instance coexistence of O 2– and H – on the same site, as shown in Ln SrCo 3+ α H β oxyhydrides ( Ln = Pr, Nd) [ 9 ].…”
Section: Specificity Of Oxyhydride Characterizationmentioning
confidence: 99%
“…This reduced evolution was attributed to the lower exciton lifetime arising from the larger amount of intrinsic anion vacancies in the PrTaON 2 lattice, along with the presence of a more reduced Ta cation. Mikita et al . recently demonstrated that synthesis of EuTiO 2 N in a nitriding atmosphere led to a metastable EuTiO 2.82 N 0.12 □ 0.06 intermediate phase (where □ denotes an anion vacancy defect) in which anion vacancies facilitated N 3− ↔O 2− exchange.…”
Section: Defect Engineering Of Perovskite Oxynitridesmentioning
confidence: 97%
“…recently demonstrated that synthesis of EuTiO 2 N in a nitriding atmosphere led to a metastable EuTiO 2.82 N 0.12 □ 0.06 intermediate phase (where □ denotes an anion vacancy defect) in which anion vacancies facilitated N 3− ↔O 2− exchange. Using a EuTiO 3 precursor this exchange resulted in a maximum N stoichiometry of 0.75, whereas a Eu 2 Ti 2 O 7 precursor decomposed into Eu 2 O 3 and uncharacterized phases . Oka et al .…”
Section: Defect Engineering Of Perovskite Oxynitridesmentioning
confidence: 97%
“…Europium can occur in oxidation states Eu II and Eu III and therefore the N/O distribution is variable. The Eu valence state can be probed with different analytical techniques like Mößbauer spectroscopy and susceptibility measurements …”
Section: Introductionmentioning
confidence: 99%